Impact of Foreign Direct Investment on Domestic Investment and Economic Growth in Iraq (1990 – 2014) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Foreign direct investment plays an important role in the activation and progress of any economy, through added value and modern means of production and advanced technology, which enters into the host country, and the importance of foreign direct investment in the Iraqi economy through structural imbalances and most of the Iraqi institutions suffer from underdevelopment and destruction as a result of circumstances Which the country has experienced Iraq has sought to attract foreign direct investment by excluding restrictions on the movement of capital and granting generous incentives to foreign investors, not only because it is an alternative or complementary source of financing for economic development, but in the transfer of advanced technological capabilities and organizational, managerial and marketing skills and other important inputs from abroad , And is a tool for integration into international networks of production, marketing and distribution and a tool to improve the international competitiveness of companies and performance  Despite the fact that Iraq is distinguished from many countries by having huge revolutions of economic and human resources as well as a large market that makes it an attractive area for foreign direct investment, the major problems facing the development of foreign investments are lack of transparency and low infrastructure as well as political and security determinants The state must address them and create an appropriate environment for attracting foreign capital.